The Fanatical Comments of NCT (Neo Culture Technology) Fans in Instagram and Twitter Pragmatic Analysis - Gustina, Riska; Raflis, Raflis (Jurnal Ilmiah Langue and Parole, 2024)
This study discusses the different ways of communicating between fanatical fans and ordinary NCT ​​fans and discusses the speech acts used. Fanaticism is always present in every activity or in every community, this research is a study of the paragmatic elements of speech acts seen from the illocutionary locutionary and perlocutionary using the theory of Stephen C. Levinson. This study aims to analyze the speech acts used by fanatic fans and ordinary fans of NCT (Neo Culture Technology). This research was conducted using a qualitative research method. The data analysis method in this study was carried out by classifying the comments on Instagram and Twitter social media. The data subjects are comments from fans from social media Instagram and NCT Dream's official twitter from posts posted on May 10 to May 12, 2022. The results show that there are 27 findings at the locutionary form of fanatical fan comments 17 ordinary fans 10, 33 illocutionary fan commentary form 19 ordinary fans 14, 24 perlocutionary fan commentary form 19 ordinary fans 6. It can be concluded that the dominant speech act used is illocutionary and is dominated by NCT ​​(Neo Culture Technology) fanatical fans.